2013
DOI: 10.1590/s1808-16572013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth and production of Pleurotus sp. in sterilized substrates

Abstract: RESUMO:O gênero Pleurotus é conhecido como cogumelo ostra, shimeji ou hiratake. Neste trabalho, com a finalidade de selecionar substratos para o cultivo de duas espécies de Pleurotus, foram avaliados vigor, crescimento micelial (cm.dia -1 ), massa fresca (g), produtividade (%) e eficiência biológica (%) de P. sajor-caju (PSC96/03) e P. ostreatoroseus (POR01/06) cultivados nos substratos: bagaço de cana-de-açú-car, capim-elefante, resíduos da cultura da mamona e palha de arroz esterilizados. As culturas fúngica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
3
8
0
3
Order By: Relevance
“…Florida exhibited visual appearance and mass suitable for commercialization. Mihai & Vamanu (2015), cultivating P. ostreatus in a substrate formulated with lignocellulosic residues, observed productivity proportional to 30%, corroborating the result obtained by the briquette of 6 tons-force, with humidity equivalent to 80% On the other hand, Bernardi et al (2013), selecting lignocellulosic raw materials for the production of substrate for oyster mushroom cultivation, found that sugarcane bagasse resulted in productivity of 1.8%, significantly lower than the averages of this research. Due to the higher productivity, an indicator that best represents the technical feasibility of substrate, briquettes of 6 and 8 tons-force, with humidity equivalent to 80%, have qualified as preferable to the axenic cultivation of oyster mushroom.…”
Section: Resultssupporting
confidence: 80%
“…Florida exhibited visual appearance and mass suitable for commercialization. Mihai & Vamanu (2015), cultivating P. ostreatus in a substrate formulated with lignocellulosic residues, observed productivity proportional to 30%, corroborating the result obtained by the briquette of 6 tons-force, with humidity equivalent to 80% On the other hand, Bernardi et al (2013), selecting lignocellulosic raw materials for the production of substrate for oyster mushroom cultivation, found that sugarcane bagasse resulted in productivity of 1.8%, significantly lower than the averages of this research. Due to the higher productivity, an indicator that best represents the technical feasibility of substrate, briquettes of 6 and 8 tons-force, with humidity equivalent to 80%, have qualified as preferable to the axenic cultivation of oyster mushroom.…”
Section: Resultssupporting
confidence: 80%
“…Twenty-six species, including Pleurotus eryngii (PE), Pleurotus citrinopileatus (PC), Pleurotus flabellatus (PFL), Pleurotus ostreatus (PO), Pleurotus djamor var. roseus (PDR), and Pleurotus florida (PF), have been reported to be cultivated using different types of lignocellulosic wastes [3][4][5][6][7][8][9][10][11]. A large number of Pleurotus species were identified and commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez et al (2008) estudiaron el comportamiento de crecimiento de la cepa P. ostreatus a 28 ºC, en un medio de cultivo agar elaborado a partir de la mezcla de dos residuos lignocelulosicos (rastrojo de tomate y paja de trigo). Midieron el crecimiento radial cada dos dias, reportando un total de 9 dias para la invasión en la caja petri, valores superiores a los reportados en esta investigacion (8 dias Bernardi et al (2013), realizaron una invasión de micelio del hongo de genero P. ostreatus en medio de cultivo CDA (pasto elefante+dextrosa+agar), a 28 ºC colonizando la caja Petri en su totalidad a los 10 días de incubacion, posteriormente utilizaron cuatro sustratos diferentes, entre ellos la cascarilla de arroz, donde reportaron una VCR de 0.883 cm h -1 en P. ostreatus durante 15 dias de incubación, equivalente a 0.3086 mm.h -1 , valores inferiores a los reportados en esta investigación. Sánchez-Santillán et al (2015), evaluaron velocidad de crecimiento radial al P. ostreatus IE8, en medio agar con extracto de bagazo de caña con y sin peptona de caseína, reportando valores de 0.406 y 0.616 mm.h -1 , respectivamente; valores inferiores a los presentados en esta investigación al adicionar peptona de caseina, pero superiores con respecto al medio elaborado sin peptona de caseina.…”
Section: Resultados Y Discusiónunclassified